The Citizens’ Constitutional Rights Regarding Habitable and Wholesome Environment: Towards a Law State that Protects the Environment - Nyoman Satyayudha Dananjaya; Fuchikawa Kazuhiko (Udayana Journal of Law and Culture, 2020)
This paper aims to examine the protection of the environment in Indonesia which is part of the realization of a law state that guarantees the constitutional rights of its citizens. It is a legal research that reviews Indonesian constitutional and statutory provisions, besides adding a comparative perspective from a Japanese Constitution and legal system. It is found that the concept of a law state in Indonesia does not specifically follow the concept of a law state like what is meant in “rechtsstaat” or “the rule of law”. It has peculiar characteristics which indeed seem to adopt the noble values ??of those two concepts which clearly confesses in the constitution along with the elements and characters stated in it. One of the most prominent characteristics of a law state is the recognition and protection of human rights. In the Indonesian Constitution 1945, human rights as the fundamental rights of human beings have been arranged and compiled which is legally legitimized become constitutional rights. Among human rights, rights related to the environment include essential rights in array of international human rights formulations. Article 28 letter H of the Indonesian Constitution 1945 expressly states the rights to habitable and wholesome environment for citizen. The protection form can be a normative arrangement in the constitution or in a formal juridical through legislation. Protection of citizens' constitutional rights related to the environment is faced with due process of environmental protection that requires consistency in order to achieve the intention and direction of the Indonesian law state itself.